Pengaruh Komunikasi dan Motivasi terhadap Kinerja Karyawan Pada PT Mandiri Sejahtera Abadi - Aji Purnomo; Sulistiyo Seti Utami (ITB Ahmad Dahlan Jakarta, 2021)
The purpose of this study was to analyze how much influence communication has on performance, motivation on performance, the influence of communication and motivation simultaneously on employee performance at PT Mandiri Sejahtera Abadi. This research design uses descriptive quantitative methods and data collection techniques library research (library research) and field research (field research). The data analysis technique used in this study was the Multiple Linear Regression and Correlation Test. The results show that the constant value is 2,960, which means that if the communication and motivation variables do not change or are almost close to 0, the work performance created is 2,960. By using the analysis of the coefficient of determination, the result is 83 percent, so it can be concluded that the communication and motivation variables have an effect on employee performance, while the remaining 17 percent is influenced by other factors outside the communication and motivation variables.